UPAYA PENINGKATAN PENDAPATAN CAFE HANA DI KECAMATAN GUGUAK KABUPATEN LIMA PULUH KOTA MELALUI STRATEGI PROMOSI - Julia Zola; Rini Elvira (CV. ADIBA AISHA AMIRA, 2025)
This research aims to find out how to increase income at Cafe Hana through promotional strategies. This research aims to formulate a promotional strategy as an effort to increase income at Cafe Hana. The type of research used is field research, namely data collected directly by the author at the research location. The informants in this research were the owner of Cafe Hana and his employees. The data analysis used is SWOT analysis, which is an analysis of the data that the author has collected through observation and interviews. The research results show that the WO strategy can be applied in an effort to increase Cafe Hana's income which has the highest weight of 4.00. Cafe Hana can take advantage of existing opportunities by reducing its weaknesses, namely: a) Maximizing promotional activities by utilizing increasingly advanced technological developments, b) Increasing or activating social media so that customers know information about Cafe Hana so that they are not less competitive with similar competitors , c) Increate promotions on social media, sunch as posting more products so that customers know information about Cafe Hana so as not to lose out to competitors and the like, d) Innovating the products offered.